The German-Austrian Philhellenism through the Revolution Press-The Case of Newspapers Ellinika Chronika (Hellenic Chronicles) and O Filos tou Nomou (The Friend of the Law) during the Period 1824-1826 - Antoniades, Euripides (My University, 2022)
The Greek Revolution of 1821 was certainly an important milestone in the history of the Greek nation in order to reclaim freedom and create an independent state. This study will attempt to highlight the significance of philhellenism and philhellenes of the diaspora, with a special emphasis on the German Austrian philhellenism, as recorded in the Greek press during the revolution. This article examines a) how two Greek newspapers portray the German-Austrian philhellenism during 1824 – 1826 and b) how this world movement of philhellenism helped during the Greek revolution. The Philhellenic movement was related to the interest of European people in Greece and pre-existed the Greek revolution of 1821. In countries of Western Europe, such as Germany and Britain, interest in classical Greece was nurtured by philosophical, philological and explorative texts and news reporting. More particularly, articles from the Ellinika Chronika (Hellenic Chronicles) and O Filos tou Nomou (The Friend of the Law) newspapers refer to cases of Philhellenes living abroad, and especially the German Austrian axis, will be examined. These items create an important field of study that showcases how the press records history and events happening at the time of the Greek Revolution, 200 years ago.
Keywords: Greece; Revolution; Uprising; Press; Struggle; Newspapers; Ellinika Chronika (Hellenic Chronicles); O Filos tou Nomou (The Friend of the Law)